Influencia De La Adición De Cobre En La Corrosión Del Cromado Metálico Para Aplicaciones En La Industria Automotríz - Núñez, Mario Alcides Lara; Lago, Segundo Manuel Espín; Villacis, Gonzalo Eduardo López; Toasa, Jorge Patricio Guamanquispe; Reyes, Jorge Isaías Caicedo; Chávez, Javier Enrique Orna (European Scientific Journal, ESJ, 2017)
At present the use of metal coatings in the automotive industry is a priority so the present research had the objective of conducting studies of metallic chromium on surfaces of rings for buses applying national and international standards. The parameters of the coating process (time, temperature and voltage) are varied to check its incidence in corrosion by checking properties such as adhesion, hardness and layer thickness. It was determined that the optimum parameters for a nickel-chromium process are 60 min, 400 C and 7V, but with low corrosion resistance, so that an alternate coating was developed to add an alkaline copper layer, obtaining three layers, copper- nickel-chromium, thereby increasing corrosion resistance.